Propuesta de Sistema de Mantenimiento basado en la metodología RCM para las plantas eléctricas tipo GPU del Grupo Aeronaval del Caribe (2022)
The Caribbean Aeronaval Group (GANCA) setbacks and delays in the operation and maintenance of its aircraft, due to the unavailability of power supply equipment on the ground (HOBART GPU Generating plants), breakdowns and unforeseen events; when there are three of these units in these facilities. In this document we make an analysis of the GANCA GPUs, considering their importance in aircraft operations. The purpose of creating a maintenance proposal is to develop a system that improves reliability and provides greater operational availability. Results were obtained where the collection, equipment classification and categorization, subsystems and systems are highlighted up to the level where, through matrices, we carry out the analysis of criticality, causes and consequences; in order to recognize, anticipate and control failure modes. With this, GANCA will have a solution for the maintenance of its GPUs, which can be used as a reference for other equipment that serves as ground support in the Colombian Naval Aviation. We conclude our document, with the delivery of the RCM proposal to GANCA, which will serve as a reference to impact the increase in availability and improve maintenance effectiveness. From a practical point of view, it is recommended to use the scheme proposed in this document.